Improving Students’ Ability to Develop ESP Materials Using Project-Based Learning Approach - Suharyanto; Ahmad Prasetyo; Luluk Lutfiyah (ELT in Focus, 2021)
English for Specific Purposes (ESP) course is taught to students of English Education Department, Universitas Muhammadiyah Surakarta. One of the aims of this course is to prepare the students to be able in designing specific course and materials for targeted students from various background and occupation. Since the pandemic, the teaching and learning process in UMS has been focused on being online both synchronous and asynchronous, including ESP course. Students are required to be able to study independently and look for learning resources beyond what has been conveyed by the lecturers. In delivering the material, teacher mostly used virtual meetings or through learning videos shared in Learning Management System. With the large number of students in the ESP class, the interaction between lecturers and students is very limited. To overcome this situation, researcher used Project Based Learning (PBL) in conducting the teaching and learning process. The project focused on designing the ESP materials for specific targeted students. The result showed that project-based learning approach is able to facilitate students to be able to improve their ability in designing the ESP materials during this pandemic situation.